Diary of a wimpy kid Greg Heffley's journal - Kinney, Jeff (Diary of a wimpy kid, 2007)
Greg records his sixth grade experiences in a middle school where he and his best friend, Rowley, undersized weaklings amid boys who need to shave twice daily, hope just to survive, but when Rowley grows more popular, Greg must take drastic measures to save their friendship.